Species-dependent Clinical Findings of Malaria Caused by Various Plasmodia in an Endemic Area of Kerman Province, Southeastern Iran - Mehdi NATEGHPOUR; Ali HOSSEININASAB; Mehrdad FARROKHNIA; Foroughieh DASTOURI; Katayun ALIDOOSTI; Dadkhoda SADEQUI; Asadollah AHMADI (Tehran University of Medical Sciences, 2017)
Background: Malaria is a big problem of public health in many tropical countries where socioeconomic development is deficient. Four species of plasmodium are capable of infecting human: P. falciparum, P. malaria, P.vivax, P. ovale. Southeastern corner of Iran, including Sistan and Baluchestan, Hormozgan and the tropical part of Kerman Province, are endemic region of malaria. This study aimed to find out clinical findings in malaria caused by various plasmodium species in moderate transmission area of southern Kerman Province. Methods: This study was conducted in health centers of Kahnooj, Manujan, Ghale-Ganj, Roudbar and Fariab in south of Kerman Province, Southeastern Iran during 2005-2009. Three hundred and thirty patients with positive malaria parasite slides entered the study. Frequencies of several malaria clinical presentations were investigated in four plasmodium species. Results: 54.2% of considered patients were male. Mean age of patients was 22.8±17.8 yr. Younger and older patient were 6 months and 80 yr, respectively. Ten patients were infected with P. falciparum, 314 with plasmodium vivax and 6 with mixed infection. The symptoms of fever, chills and sweating were present in 74.6% of subjects. Other complaints were joint pain, headache, fatigue, vomiting, and diarrhea. Splenomegaly was detected in 17.57% of the individuals. Conclusion: Malaria should be considered in differential diagnosis of all acutely febrile patients in endemic area. Classic symptoms of fever, chills and sweating may not present in all of patients.